2021
DOI: 10.1128/msphere.00203-21
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID-19 Severity with a Specific Nucleocapsid Antibody plus Disease Risk Factor Score

Abstract: The COVID-19 pandemic has resulted in over two million deaths worldwide. Despite efforts to fight the virus, the disease continues to overwhelm hospitals with severely ill patients.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 56 publications
5
20
1
Order By: Relevance
“…Several studies have reported that biased humoral N-reactive response could lead to poor prognosis [44,45]. In this study, we described a contrasting pattern between the serum and the MBC compartment reactive to SARS-CoV-2 N. IgM response to N exhibited lower magnitude, consistent with what have been previously reported [38], raising questions on the characteristics of N-reactive B cells that respond to infection.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have reported that biased humoral N-reactive response could lead to poor prognosis [44,45]. In this study, we described a contrasting pattern between the serum and the MBC compartment reactive to SARS-CoV-2 N. IgM response to N exhibited lower magnitude, consistent with what have been previously reported [38], raising questions on the characteristics of N-reactive B cells that respond to infection.…”
Section: Discussionsupporting
confidence: 86%
“…We wondered whether low anti-RBD reactivity levels observed in this cohort is because the cases were mild. Indeed, we have reported that that elevated levels of antibody against a SARS-CoV-2 NP epitope predicts disease severity in COVID-19 patients 19 . Consequently, we compared the antibody levels among 93 hospitalized individuals who were either in intensive care or not and the results are shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings may also imply convalescent plasma collections (e.g., CCP units with greater NL63 antibody responses and lower HKU1 antibodies) had higher neutralizing antibodies to the SARS-CoV-2 receptor-binding domain (RBD) [38]. Another study found better outcomes in recipients of CCP units with higher anti-NL63 or anti-OC43 antibodies [39]; Influenza virus A(H 3 N 2 ): Antibody binding to an epitope region from SARS-CoV-2 nucleocapsid, termed Ep9, is associated with greater COVID-19 disease severity [40]. Bioinformatics analysis identified the neuraminidase protein (not present in the influenza vaccine) of influenza virus A(H3N2) as responsible, a strain that circulated widely in 2014 [41]; Acute malaria infection: Plasmodium infection induces cross-reactive antibodies to carbohydrate epitopes on the SARS-CoV-2 spike protein [42]; Natural ABO isoagglutinins: The ABO blood group affects COVID-19 incidence and severity, as well as the type and duration of the cellular immune response [43].…”
Section: • Pathogensmentioning
confidence: 99%